Modes of address and pronominal usage in Punjabi : A Sociolinguistics Study - Omkar N. Koul (Central Institute of Indian Languages Mysore, 1989)
The book discusses about the impact of social change in the society and language.
Keywords: Punjabi; Modes of Address And Pronominal Usage In Punjabi : A Sociolinguistics Study; Sociolinguistics; Punjabi; English